Design and Realization of Solar Power Systems using Photovoltaic Cells for Smart Plantation Watering Systems - Rezky Maruli Purba; Nafisah, Suratun; Uri Arta Ramadhani; Kisna Pertiwi (Jurnal Multidisiplin Madani, 2023)
The development of plants on a plantation is highly dependent on providing sufficient water for the plants.Hence, it is needed to have a optimal smart watering for plantation that is able to distribute water for plants efficiently. In this work, we developed an off-grid solar power plant to support a smart watering system. This solar power plant uses polycrystalline panels that function to absorb solar energy. Second, there is the SCC (Solar Charge Controller) which is used to charge the battery and regulate power from the battery to the load to keep the battery from overcharging. Then there is a 500 watt psw inverter. The battery is also used as a storage of the power that has been generated. The power that has been stored in this battery still be used to turn on the pump to water the plants, and it is also useful to turn on the existing sensors which will be input to the microcontroller then give the command to turn on the pump. Based on the collected data, it is known that the system requires an average power of 783.56 W for one hour